Primary Prevention of Cardiovascular Risk in Lithuania—Results from EUROASPIRE V Survey - Gediminas Urbonas; Lina Vencevičienė; Leonas Valius; Ieva Krivickienė; Linas Petrauskas; Gintarė Lazarenkienė; Justina Karpavičienė; Gabrielė Briedė; Emilė Žučenkienė; Karolis Vencevičius (Medicina, 2020)
Background and Objectives: Cardiovascular disease (CVD) prevention guidelines define targets for lifestyle and risk factors for patients at high risk of developing CVD. We assessed the control of these factors, as well as CVD risk perception in patients enrolled into the primary care arm of the European Action on Secondary and Primary Prevention by Intervention to Reduce Events (EUROASPIRE V) survey in Lithuania. Materials and Methods: Data were collected as the part of the EUROASPIRE V survey, a multicenter, prospective, cross-sectional observational study. Adults without a documented CVD who had been prescribed antihypertensive medicines and/or lipid-lowering medicines and/or treatment for diabetes (diet and/oral antidiabetic medicines and/or insulin) were eligible for the survey. Data were collected through the review of medical records, patients’ interview, physical examination and laboratory tests. Results: A total of 201 patients were enrolled. Very few patients reached targets for low-density lipoprotein cholesterol (LDL-C) (4.5%), waist circumference (17.4%) and body mass index (15.4%). Only 31% of very high CVD risk patients and 52% of high-risk patients used statins. Blood pressure target was achieved by 115 (57.2%) patients. Only 21.7% of patients at very high actual CVD risk and 27% patients at high risk correctly estimated their risk. Of patients at moderate actual CVD risk, 37.5% patients accurately self-assessed the risk. About 60%−80% of patients reported efforts to reduce the intake of sugar, salt or alcohol; more than 70% of patients were current nonsmokers. Only a third of patients reported weight reduction efforts (33.3%) or regular physical activity (27.4%). Conclusions: The control of cardiovascular risk factors in a selected group of primary prevention patients was unsatisfactory, especially in terms of LDL-C level and body weight parameters. Many patients did not accurately perceive their own risk of developing CVD.